The Cultural and Financial Dynamics of Female Entrepreneurs as Well as Their Empowering Ventures - Andalib, Tarnima W.; Hossain, Syed Arman; Ramayah, T.; Azizan, Noor A.; Hassan, Dauwood I.; Khawar, Sara (Emerging Science Journal, 2025)
This research examines how female entrepreneurs in Bangladesh navigate the cultural, social, and financial challenges of F-commerce, where informal digital platforms like Facebook and Instagram have become vital spaces for women-led businesses. In addition, despite the growth of digital entrepreneurship, existing models such as the gendered growth framework and ‘TOCOM contingency model’ often overlook how localized cultural dynamics shape women’s entrepreneurial experiences. To bridge this gap, this research explores how these dynamics influence not only the constraints female entrepreneurs face, but also the motivations and resilience strategies that drive their success. However, grounded in ‘Consumer Culture Theory’ and enriched by anthropological perspectives, this research uses a qualitative approach, featuring instrumental case studies and in-depth interviews. The analysis, conducted through NVivo coding, captures both the lived realities and the strategic digital engagements of these women. Although the outcome is a proposed conceptual framework that links culture, motivation, and F-commerce participation offering insight into how female entrepreneurs adapt, persist, and redefine their roles in the digital economy. Therefore, this research also outlines practical recommendations to enhance digital inclusion and gender equity through skills training, mentorship, as well as policy support.